Desempenho de cultivares de girassol em função do manejo da adubação nitrogenada e potássica em condições edafoclimáticas na savana de Boa Vista, em Roraima - Ivanoff, Maria Elena Almeida (2009)
Sunflower (Helianthus annuus L.), due it presents important agronomical characteristics such as high oil content, low water requirement and due the possibility of being cultivated in different times of the year, can become an important crop option for the production. The culture is still regarded as secondary in by brazilian productives system and it lacks more research, mainly on fertility management. To this end, two experiments were conducted in the Center of Agricultural Sciences of Universidade Federal de Roraima, located in Boa Vista – RR in 2007 and 2008. The approach used in the work was the delineation of randomized blocks in factorial scheme with four replicates. The first experiment aimed at evaluating the production components of three cultivars of sunflower (Agrobel 960, Agrobel 962 and Embrapa 122/V2000), submitted to four forms of nitrogen application, being: 100% 20 days after sowing (DAS) - (0-100-0-0); 30% at sowing and 70% 20 DAS - (30-70-0-0); 30% at sowing, 30% 20 DAS and 40% 40 DAS (30-30-40-0); 20% in sowing, 30% 20 DAS, 30% 40 DAS and 20% 60 DAS (20-30-30-20). N application form affected all production components outstanding treatment (30-70-0-0), which was superior for all variables studied. Treatment (30-30-40-0) presented results comparable to (30-70-0- 0). The application form (20-30-30-20) determined the worst performance for the variables. Varietal effect was observed only for the variables height of plant and height of capitulum. The productivity average obtained was 1.639 kg ha-1 and there was no superiority of hybrids Agrobel 960 and Agrobel 962 in relation to variety Embrapa 122/V2000. The aim of the second experiment was to study production components of three cultivars of sunflower submitted to different rates of potassium side dressing. The treatments consisted of a combination of three varieties (Agrobel 960, Agrobel 967 and Embrapa 122/V2000) and five doses of potassium sidedressing (0; 30; 60; 90 and 120 kg ha-1). The effects of K sidedressing rates were independent from the effects of cultivars. Hybrid Agrobel 967 presented superiority in relation to hybrid Agrobel 960 and variety Embrapa 122/V2000 concerning to productivity of achenes, oil and oil content. The rates of potassium in sidedressing provided linear-quadratic increase among variables studied, except for height of the capitulum. The rate of maximum technical efficiency for productivity of achenes, oil content and oil productivity varied from 83,8 to 85.6 kg ha-1 of K2O. Maximum productions achieved by adding increasing rates of K2O were 2.038,3 kg ha-1 of achenes with 52,5% of oil in seed and 1.079,3 kg ha-1 of oil yield.